POLITICAL STRATEGY OF THE WINNING TEAM OF RATU DEWA AND PRIMA SALAM IN THE 2024 PALEMBANG CITY REGIONAL HEAD ELECTION - Jasika, Jasika; Budianto, Kun; Anisyah, Siti (Asosiasi Prodi Manajemen Administrasi Pendidikan Indonesia (APMAPI), 2025)
In the dynamics of local politics in Indonesia, campaign strategy is a crucial factor in determining the success of candidates in the Regional Head Election (Pilkada). This study aims to analyze the political strategies implemented by the winning teams of Ratu Dewa and Prima Salam in the 2024 Palembang City Elections. Using a descriptive qualitative approach, data was collected through in-depth interviews, field observations, and documentation with informants from the success team, community leaders, and residents of Palembang City. The results of the study identified three main strategies, namely push political, pull political, and pass political. The push political strategy is carried out through direct approaches such as door-to-door campaigns and open discussions. The pull political strategy utilizes mass media and social media to convey campaign messages and reach young voters. Meanwhile, the political pass is realized through cooperation with influential figures and community organizations. The simultaneous implementation of all three strategies has been proven to increase public engagement and strengthen the candidate's position. This study recommends the importance of two-way communication, campaign content innovation, and periodic evaluation to increase the effectiveness of political strategies in electoral contests.